2016
DOI: 10.1161/jaha.116.003551
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite Therapy Ameliorates Myocardial Dysfunction via H 2 S and Nuclear Factor‐Erythroid 2‐Related Factor 2 (Nrf2)‐Dependent Signaling in Chronic Heart Failure

Abstract: BackgroundBioavailability of nitric oxide (NO) and hydrogen sulfide (H2S) is reduced in heart failure (HF). Recent studies suggest cross‐talk between NO and H2S signaling. We previously reported that sodium nitrite (NaNO 2) ameliorates myocardial ischemia‐reperfusion injury and HF. Nuclear factor‐erythroid‐2‐related factor 2 (Nrf2) regulates the antioxidant proteins expression and is upregulated by H2S. We examined the NaNO 2 effects on endogenous H2S bioavailability and Nrf2 activation in mice subjected to is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 71 publications
(128 reference statements)
0
24
0
Order By: Relevance
“…Another important cause of HF in patients with T2DM is myocardial infarction due to coronary artery disease, with nitrite displaying a potential role in coronary ischaemia–reperfusion injury (IRI) , acute ST‐elevation myocardial infarction (STEMI) and remote ischaemic preconditioning (RIPC) . Moreover, it was shown that chronic, 4–9 weeks' oral sodium nitrite supplementation prevented the increases in end‐diastolic volume (EDV) and end‐systolic volume (ESV) in murine models of IRI following left coronary artery occlusion , and also prevented pressure overload‐induced LV hypertrophy (LVH) with trans‐aortic constriction .…”
Section: Introductionmentioning
confidence: 99%
“…Another important cause of HF in patients with T2DM is myocardial infarction due to coronary artery disease, with nitrite displaying a potential role in coronary ischaemia–reperfusion injury (IRI) , acute ST‐elevation myocardial infarction (STEMI) and remote ischaemic preconditioning (RIPC) . Moreover, it was shown that chronic, 4–9 weeks' oral sodium nitrite supplementation prevented the increases in end‐diastolic volume (EDV) and end‐systolic volume (ESV) in murine models of IRI following left coronary artery occlusion , and also prevented pressure overload‐induced LV hypertrophy (LVH) with trans‐aortic constriction .…”
Section: Introductionmentioning
confidence: 99%
“…The Nrf2-ARE signaling pathway is recognized to be the most important endogenous anti-oxidative stress pathway (20). Activation of this pathway can induce the production of antioxidant enzyme and phase II drug metabolic enzyme (21). It plays a vital role in maintaining intracellular redox state, reducing oxidative damage and protecting cell function.…”
Section: Discussionmentioning
confidence: 99%
“…SPRC is a new type of endogenous H 2 S controlled-release preparation that protects rat HF from left coronary occlusion by maintaining levels of antioxidant molecules such as GSH, CAT, and SOD ( Huang et al, 2013 ). NaNO 2 significantly improved ischemia-induced left ventricular function in CHF mice by increasing H 2 S bioavailability, Nrf2 activation, and antioxidant defense ( Donnarumma et al, 2016b ). In addition, Na 2 S treatment inhibits ischemic heart failure in mice by inhibiting nuclear export of histone deacetylase 4 and apoptotic signaling kinase-1 signaling in a thioredoxin 1 dependent manner ( Nicholson et al, 2013 ).…”
Section: H 2 S and Cardiovascular Diseasesmentioning
confidence: 99%